Gender differences in brain type according to the Empathy/Systemising Quotient for Children (EQ/SQ-C) questionnaire in Indonesia. Issue 2 (1st September 2020) - Chaidir, Kamila Ratu; Nathania, Eloisa; Mahdiyyah, Kindah; Phallavi, Yudi Rheza; Wiguna, Tjhin
Abstract : Objective: This research was conducted to support the hypothesis that boys and girls have different brain types that affect their empathy and systemising quotients. Method: This was a cross-sectional study using an online survey. The Indonesian version of the Empathy/Systemising Quotient for Children (EQ/SQ-C) questionnaire was used to identify the brain type and empathy and systemising quotients. Participants were 620 parents who had primary school children and having minimal junior high school background. The data analysis used chi-square test and Mann–Whitney U -test on SPSS program for Mac version 20. Results: Boys and girls had different brain types ( p < 0.05). The extreme-empathising brain type consisted of 1.9% girls and 0.5% boys; the empathising brain type was 15.8% in girls and 9.0% in boys. Further, 0.8% of girls and 2.6% of boys had the extreme-systemising brain type. Although the empathy quotient average mean score of the boys was significantly lower than the girls ( p < 0.05), the systemising quotient average mean score was slightly higher than that of the girls. Conclusion: This study found that gender plays an important role in empathy and systemising skills. Therefore, creating a stimulating program that supports empathy and systemising quotients in primary school students should be developed according to gender.